Literalingua Program: Teacher and Student Literacy Assistance at Sanggar Learning Sentul Malaysia - Ihsan Nugroho; Miftakhul Huda; Yasir Sidiq; Naufal Ishartono; Zainal Arifin; Evi Dwi Kartikasari; Izzatul Azmi Mulya; Temon Bagus Hidayatullah; Dicky Eka Prasetya (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Every child has the right to learn regardless of whose parents they were born. Children of Indonesian Migrant Workers (TKI) who work abroad also have the right to study in general. Many factors hinder the children of foreign migrant workers from being able to attend school, one of which is the lack of Indonesian schools abroad. The Community Service Program (KKN) was held at the Sentul Guidance Studio in Malaysia for almost one month. This service program aims to increase basic literacy and introduce Indonesian culture to children at SB Sentul. The partner in this service is from the management of SB Sentul, namely Mr. Shohenuddin as the administrator of SB Sentul. This service used the Special Guidance observation method. Special Tutoring Activities are activities that aim to focus on teaching children who need special attention, such as for example it is difficult to understand the material presented, they speak a foreign language every day so that Indonesian is difficult to understand, etc. This activity is carried out every Monday-Friday and of course this activity requires a long process and a teacher must have full patience. The results obtained by the children have increased in terms of their basic literacy and the children are getting to know their culture, namely Indonesian culture